A randomized controlled trial of rollator-style walkers and oxygen in chronic obstructive pulmonary disease - Waldegger, Lisa Marie (University of Ottawa (Canada), 2003)
Statement of problem. The ability to walk, fundamental to a good quality of life, is affected by chronic obstructive pulmonary disease. Results. Eleven participants were recruited (May 2001 to January 2002) from a tertiary rehabilitation centre. The patients mean age (+/-standard deviation) was 67.5 +/- 16.6 years, mean percent predicted forced expiratory velocity in one second (FEV1.0) was 26.1 +/- 6.8%, and mean PaO2 was 61.2 +/- 2.3 mMHg. There were no significant period by treatment interactions, or period effects on any outcome. Oxygen significantly outperformed the rollator-style walker on final oxygen saturation (7.8 percent (95% CI 5.0 to 10.6)) and perceived exertion (1.3 points (95% CI 0.1 to 2.4)) but there was no difference noted on distance walked (22.2 metres (95% CI: -76.7 to +32.4)) or speed (-0.02 metres/second (95% CI: -0.13 to 0.08)). Compared to unassisted walks, oxygen improved distanced walked (51.3 metres (95% CI 18.6 to 84.0)) but rollator-style walkers did not (31.4 metres (95% CI -3.4 to 66.2)). Participants indicated that both interventions improved their walking but more participants preferred the rollator-style walker. Conclusions. In spite of oxygen reducing arterial desaturation, rollator-style walkers resulted in similar distance walked compared to oxygen. However, when compared to unassisted walks, oxygen appears to be more effective in increasing distance walked. Rollator-style walkers are a lower cost alternative to oxygen in individuals with COPD and exertional desaturation whose resting arterial oxygen is between 55--65 mmHg. (Abstract shortened by UMI.)
Keywords: Health Sciences, Rehabilitation and Therapy.; Health Sciences, Public Health.